Application of Sapta Pesona in Realizing Guava Picking Tourist Destinations: Penerapan Sapta Pesona dalam Mewujudkan Destinasi Wisata Petik Jambu - Alfianto, Mochamad Rizal; Purwati, Suci; Kamila, Syafa Tasya; Supriyadi (Universitas Muhammadiyah Sidoarjo, 2022)
Tourism is the sector most affected by the COVID-19 pandemic. This condition occurs all over the world with different scales and dimensions. With the existence of Sapta Pesona, which are seven conditions that need to be realized and promoted in people's daily lives, it can increase the attractiveness and competitiveness of tourism. This refers to the support and role of the community as hosts to create an environment and atmosphere that can encourage the growth and development of the tourism industry through the realization of the seven elements. Kebaron Village is one of the villages with a guava plantation destination in Sidoarjo, with a very abundant guava product. Various types of guava are planted on an area of ​​5.5 hectares in this village of Kebaron Sidoarjo, and there are around 1,200 guava trees. The obstacle experienced by guava picking tourism in Kebaron village is the decrease in visitors since the Covid-19 pandemic which took place from early 2020, it is necessary to increase and renew the garden area by adding some supporting infrastructure. Based on the analysis conducted with partners, there are several problems that need to be addressed immediatel.